2022
DOI: 10.3390/birds3040026
|View full text |Cite
|
Sign up to set email alerts
|

Bird Assemblages in a Peri-Urban Landscape in Eastern India

Abstract: Urbanization plays an important role in biodiversity loss across the globe due to natural habitat loss in the form of landscape conversion and habitat fragmentation on which species depend. To study the bird diversity in the peri-urban landscape, we surveyed four habitats—residential areas, cropland, water bodies, and sal forest; three seasons—monsoon, winter, and summer in Baripada, Odisha, India. We surveyed from February 2018 to January 2019 using point counts set along line transects; 8 transects were esta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Retaining established native trees has also been reported to be effective in maintaining higher bird diversity in new urban centres (Barth et al 2015). Karjee et al (2022) conducted a study in a peri-urban area of east India and found that agricultural fields and degraded croplands helped maintain bird diversity. Increase in road cover, green cover and tree count had a positive impact on invasive species while tree species richness decreased the abundance of invasive bird species.…”
Section: Materials and Methods Study Areamentioning
confidence: 99%
“…Retaining established native trees has also been reported to be effective in maintaining higher bird diversity in new urban centres (Barth et al 2015). Karjee et al (2022) conducted a study in a peri-urban area of east India and found that agricultural fields and degraded croplands helped maintain bird diversity. Increase in road cover, green cover and tree count had a positive impact on invasive species while tree species richness decreased the abundance of invasive bird species.…”
Section: Materials and Methods Study Areamentioning
confidence: 99%
“…Urban land expansion, infrastructure development, and population growth have destroyed habitats and natural habitat loss (Laurance et al 2015;Simkin et al 2022). However, despite the threat of urbanization, peri-urban areas remain crucial in preserving biodiversity, particularly bird species (Karjee et al 2022). It has been widely asserted that peri-urban areas support diverse bird species, including remnant natural habitats, green belts, and reservoirs (Evans and Evans 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Peri-urban areas frequently provide various habitat types, including farmlands, urban parks, and forests, which can support various bird species (Canedoli et al 2017;Canedoli et al 2018;Karjee et al 2022). However, rapid urbanization and environmental changes seriously challenge bird populations (Sol et al 2014).…”
Section: Introductionmentioning
confidence: 99%